"SUSCEPTIBILITY OF DIFFERENT FIELD STRAINS OF BLATTELLA GERMANICA TO FOUR PYRETHROIDES (ORTHOPTERA: BLATTELLIDEA)" - H. Ladonni (Tehran University of Medical Sciences, 1997)
The susceptibility of 5 wild strains of German cockroach collected from five infected flats in Tehran were assessed by tests of surface contact method to cyfluthrin, permethrin, sumithrin and lambdacyhalothrin. Comparison of the result of knockdown tests on the wild strains with a standard susceptible strain indicated that all the strains are resistant to sumithrin, i.e., resistance ratio, the RR, ranged from 309 to 7.75 folds; but susceptible to beta - cyfluthrin (RR < 1.5). Permethrin tests on the field collected strains revealed that 3 out of 5 strains are resistant (RR = 2.9 to 3 folds) but two are tolerant to permethrin (RR ranged between 2.24 to 2.5 folds). Further tests on the lambdacyhalothrin showed that 4 out of 5 strains were tolerant and one is susceptible. It could be concluded that development of permethrin and lambdacyhalothrin resistance/tolerance in a number of strains of German cockroach was as the result of direct use of these later insecticides in human dwelling. Sumithrin resistance is unlikely related to use of such small amount of this compound in cockroach control programs; but it is likely related to uses of other pyrethroids and hence developing cross-resistance to sumitlirin.